GMP-Grade Manufacturing of T Cells Engineered to Express a Defined γδTCR - Straetemans, Trudy; Kierkels, Guido J. J.; Doorn, Ruud; Jansen, Koen; Heijhuurs, Sabine; dos Santos, Joao M.; van Muyden, Anna D. D.; Vie, Henri; Clemenceau, Béatrice; Raymakers, Reinier; de Witte, Moniek; Sebestyén, Zsolt; et al. (Frontiers in Immunology, 2018)
γ9δ2T cells play a critical role in daily cancer immune surveillance by sensing cancer mediated metabolic changes. However, a major limitation of the therapeutic application of γ9δ2T cells is their diversity and regulation through innate co-receptors. In order to overcome natural obstacles of γ9δ2T cells, we have developed the concept of T cells engineered to express a defined γδT cell receptor (TEGs). This next generation of chimeric antigen receptor engineered T (CAR-T) cells not only allows for targeting of hematological, but also of solid tumors, and therefore overcomes major limitations of many CAR-T and γδT cell strategies. Here we report on the development of a robust manufacturing procedure of T cells engineered to express the high affinity Vγ9Vδ2T cell receptor (TCR) clone 5 (TEG001). We determined the best concentration of anti-CD3/CD28 activation and expansion beads, optimal virus titer and cell density for retroviral transduction, and validated a GMP-grade purification procedure by utilizing the CliniMACS system to deplete non- and poorly-transduced T cells. To the best of our knowledge, we have developed the very first GMP manufacturing procedure in which αβTCR depletion is used as a purification method, thereby delivering untouched clinical grade engineered immune cells. This enrichment method is applicable to any engineered T cell product with a reduced expression of endogenous αβTCRs. We report on release criteria and the stability of TEG001 drug substance and TEG001 drug product. The GMP-grade production procedure is now approved by Dutch authorities and allows TEG001 to be generated in cell numbers sufficient to treat patients within the approved clinical trial NTR6541. NTR6541 will investigate the safety and tolerability of TEG001 in patients with relapsed/refractory acute myeloid leukemia, high-risk myelodysplastic syndrome and relapsed/refractory multiple myeloma.